Utilization of Digital Marketplaces in a Strategy to Increase the Probability of Market Access for Risol MSMEs in Bekasi - Andriani, Meta; Maharani, Adinda Ayu Tri Kartika; Efrita, Azizah Putri; Puspitasari, Dian (Formosa Journal of Applied Sciences, 2024)
The Micro, Small and Medium Enterprises (MSME) sector has a significant role in contributing to Gross Domestic Product (GDP). Even though almost all individuals are now involved in online activities or using mobile devices, the majority of MSMEs still rely on conventional marketing methods. Lack of understanding of digitalization trends is a major obstacle. This research aims to provide assistance, increase knowledge and implement digital marketing to support the growth of MSMEs. It is hoped that this approach can provide relevant information and increase MSME income, overcome digital barriers, and optimize market potential. The implementation of digital marketing strategies is expected to increase the competitiveness of MSMEs in an increasingly digitalized business ecosystem.